l-Triiodothyronine and l-Reverse-Triiodothyronine Generation in the Human Polymorphonuclear Leukocyte - Woeber, Kenneth A. (1978)
Extrathyroidal monodeiodination of l-thyroxine (T(4)) is the principal source of l-triiodothyronine (T(3)) and l-reverse-triiodothyronine (rT(3)) production. To define some of the cellular factors involved, we examined T(3) and rT(3) generation from added nonradioactive T(4) in human polymorphonuclear leukocytes, using radioimmunoassays to quantify the T(3) and rT(3) generated. Under optimum incubation conditions which included a pH of 6.5 in sucrose-acetate buffer, the presence of dithiothreitol as a sulfhydryl-group protector, and incubation in an hypoxic atmosphere, significant net generation of T(3) and rT(3) was observed. Of the several subcellular fractions studied, the particulate fraction obtained by centrifugation at 27,000 g was found to possess the highest T(3)- and rT(3)-generating activities per unit quantity of protein. With respect to T(3) generation from substrate T(4), the K(m) was 5 μM and the V(max) was 7.2 pmol/min per mg protein. Propylthiouracil, methimazole, and prior induction of phagocytosis inhibited both T(3) and rT(3) generation, but T(3) generation was inhibited to a greater extent. rT(3), in a concentration equimolar to that of substrate T(4), did not alter T(3) generation, but inhibited T(3) generation when the molar ratio of rT(3) to T(4) approached 10:1. Under the incubation conditions employed, particulate fractions of leukocytes obtained from five cord blood samples displayed an essentially normal relationship between T(3)- and rT(3)-generating activities, despite the distinctly divergent serum T(3) and rT(3) concentrations in these samples. From our findings, we draw the following conclusions: (a) the human polymorphonuclear leukocyte possesses the ability to generate T(3) and rT(3) from substrate T(4); (b) the T(3)- and rT(3)-generating activities are associated principally with the 27,000 g particulate fraction and display enzymic characteristics with a sulfhydryl-group requirement; (c) T(3)-generating activity appears to be more susceptible to inhibitory influences than rT(3)-generating activity; and (d) in cord blood leukocytes, the putative enzymes catalyzing T(3) and rT(3) generation appear to be functionally intact under the experimental conditions employed.